The steroid-inducible pOp6/LhGR gene expression system is fast, sensitive and does not cause plant growth defects in rice (Oryza sativa) - Samalova, Marketa; Moore, Ian (BMC plant biology, 2021)
Inducible systems for transgene expression activated by a chemical inducer or an inducer of non-plant origin are desirable tools for both basic plant research and biotechnology. Although, the technology has been widely exploited in dicotyledonous model plants such as Arabidopsis, it has not been optimised for use with the monocotyledonous model species, namely rice. We have adapted the dexamethasone-inducible pOp6/LhGR system for rice and the results indicated that it is fast, sensitive and tightly regulated, with high levels of induction that remain stable over several generations. Most importantly, we have shown that the system does not cause negative growth defects in vitro or in soil grown plants. Interestingly in the process of testing, we found that another steroid, triamcinolone acetonide, is a more potent inducer in rice than dexamethasone. We present serious considerations for the construct design to avoid undesirable effects caused by the system in plants, leakiness and possible silencing, as well as simple steps to maximize translation efficiency of a gene of interest. Finally, we compare the performance of the pOp6/LhGR system with other chemically inducible systems tested in rice in terms of the properties of an ideal inducible system.
Keywords: Transgenes; GVG; zemědělské plodiny; rýže (rod); Oryza; Crops, Agricultural; transgeny; rostlinné geny; Glucocorticoid; XVE; Plant Development; dexamethason; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Promotor; Dexamethasone; Chemically inducible gene expression; Monocots; vývoj rostlin; Genes, Plant